Application of isotopic and elemental fingerprints in identifying the geographical origin of goat milk in China. (30th March 2019) - Liu, Hongyan; Zhao, Qingyu; Guo, Xiaoqing; Tang, Chaohua; Yu, Xiaonan; Zhan, Tengfei; Qin, Yuchang; Zhang, Junmin
Highlights: Goat milk, feed, soil and drinking water from three regions in China were determined. Significant correlation was found for δ 13 C between casein and lipid. Significant correlation was found for δ 2 H between casein and milk water. The δ 2 H and δ 18 O in casein and milk water were identical to that in drinking water. 100% correct classification rate among three regions was obtained by 7 key variables. Abstract: In the study, the samples of goat milk, feed, soil and drinking water were firstly collected from nine farms of three provinces in China, the stable isotopic ratios (δ 13 C, δ 15 N, δ 2 H and δ 18 O) in casein, lipid of milk, feed, and drinking water and the contents of 11 elements in milk and soil were determined. Statistical analysis indicated that except the content of Zn, other variables in milk showed significant differences among two or three regions. Significant correlations were found for δ 13 C between casein and lipid (r = 0.953, P  < 0.05) and for δ 2 H between casein and milk water (r = 0.816, P  < 0.05). The δ 2 H and δ 18 O in casein and milk water were identical to that in corresponding drinking water. Finally, seven key variables (δ 15 Ncasein, δ 18 Ocasein, Ni, Se, Rb, Sr and Ba) were selected by stepwise canonical discriminant analysis and the correct classification rate reached 100%.